2014
DOI: 10.1016/j.cub.2014.10.031
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway Regulates Hematopoiesis in Drosophila melanogaster

Abstract: SUMMARY The Salvador-Warts-Hippo (Hippo) pathway is an evolutionarily conserved regulator of organ growth and cell fate. It performs these functions in epithelial and neural tissues of both insects and mammals, and in mammalian organs such as the liver and heart. Despite rapid advances in Hippo pathway research, a definitive role for this pathway in hematopoiesis has remained enigmatic. The hematopoietic compartments of Drosophila melanogaster and mammals possess several conserved features [1, 2]. D. melanogas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 44 publications
11
38
0
Order By: Relevance
“…LATS2 is a member of the Hippo signaling pathway that is of outmost importance during development and early reports associated this pathway with hematopoiesis. [45] Consistently, we found that similar to p21 CIP1 also LATS2 mRNA expression is significantly decreased in NB4 RBM38 knockdown cells upon ATRA treatment (Additional file 3: Figure S2b). Thus, decreased LATS2 expression due to reduced RBM38 levels may also contribute to an immature myeloid phenotype.…”
Section: P21 Cip1 (Cdkn1a) and Lats2 Mrna Levels Are Significantly Desupporting
confidence: 76%
“…LATS2 is a member of the Hippo signaling pathway that is of outmost importance during development and early reports associated this pathway with hematopoiesis. [45] Consistently, we found that similar to p21 CIP1 also LATS2 mRNA expression is significantly decreased in NB4 RBM38 knockdown cells upon ATRA treatment (Additional file 3: Figure S2b). Thus, decreased LATS2 expression due to reduced RBM38 levels may also contribute to an immature myeloid phenotype.…”
Section: P21 Cip1 (Cdkn1a) and Lats2 Mrna Levels Are Significantly Desupporting
confidence: 76%
“…Previous reports have demonstrated the importance of the Hippo pathway in fly hematopoiesis. 25,26 It was also reported that key proteins of the Hippo pathway are expressed in mantle cell lymphoma. 27 Furthermore YAP, a key component of the Hippo pathway, is highly expressed in stem cells and decreases progressively during differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Warts -knockout animals exhibit premature differentiation and overproliferation of lymph gland cells 43. Similarly, in Xenopus Mst1 -knockdown model, erythropoiesis, myelopoiesis and vasculogenesis were interrupted, but the stem cell or haematopoietic progenitor populations were maintained, suggesting that it is necessary to block Yap via Mst1 regulation during haematopoietic and endothelial cell differentiation 44…”
Section: Hippo Pathway's Role In Haematopoiesis and The Pathophysiolomentioning
confidence: 99%